Regime-switching global vector autoregressive models - Michael Binder; Marco Gross (European Central Bank (ECB), 2013)
The purpose of the paper is to develop a Regime-Switching Global Vector Autoregressive (RS-GVAR) model. The RS-GVAR model allows for recurring or non-recurring structural changes in all or a subset of countries. It can be used to generate regime-dependent impulse response functions which are conditional upon a regime-constellation across countries. Coupling the RS and the GVAR methodology improves out-of-sample forecast accuracy significantly in an application to real GDP, price inflation, and stock prices.
Keywords: C32; E17; G20; 330; forecasting and simulation; Global macroeconometric modeling; nonlinear modeling; Regime switching